The Composite of 3, 4-Dihydroxyl-Phenyl Lactic Acid and Notoginsenoside R1 Attenuates Myocardial Ischemia and Reperfusion Injury Through Regulating Mitochondrial Respiratory Chain - Yan, Li; Pan, Chun-Shui; Liu, Yu-Ying; Cui, Yuan-Chen; Hu, Bai-He; Chang, Xin; Wei, Xiao-Hong; Huang, Ping; Liu, Jian; Fan, Jing-Yu; Li, Quan; Sun, Kai; et al. (Frontiers in Physiology, 2021)
Aim: 3, 4-dihydroxyl-phenyl lactic acid (DLA) and notoginsenoside R1 (R1) are known to protect ischemia and reperfusion (I/R) injury by targeting Sirt-1/NDUFA10 /Complex I and ROCK/ATP synthase δ subunit (ATP5D), respectively. We hypothesized that a composite of the two may exhibit a more potent effect on I/R injury. The study was designed to test this hypothesis. Materials and methods: Male Sprague-Dawley rats underwent left anterior descending artery occlusion and reperfusion, with or without DLA, R1 or DR pretreatment. Heart function, myocardial morphology, myocardial infarct, myocardial blood flow (MBF), and apoptosis,vascular diameter and red blood cell (RBC) velocity in venules were evaluated. MPO, MDA, 8-OHdG were assessed. The content of ATP, ADP and AMP, the activity of mitochondrial respiratory chain Complex I and its subunit NDUFA10, Complex V and its subunit ATP5D, Sirt-1, RhoA, ROCK-1, P-MLC were evaluated. R1 binding to Sirt-1 was determined by Surface Plasmon Resonance (SPR). Results: DLA inhibited the expression of Sirt-1, the reduction in Complex I activity and its subunit NDUFA10 expression, the increase in MPO, MDA, 8-OhdG and apoptosis. R1 inhibited the increase in the expression of RhoA/ROCK1/P-MLC, the reduction of Complex V activity and its subunit ATP5D expression, alleviated F-actin and myocardial fibers rupture. Both of DLA and R1 reduced the myocardial infarction size, increased the velocities of RBC in venules, improved MBF and heart function impaired by I/R. DR exhibited effects similar to what exerted, respectively, by DLA and R1 in terms of respiratory chain complexes and related signaling and outcomes, and an even more potent effect on myocardial infarct size, RBC velocity, heart function and MBF than DLA and R1 alone. Conclusion: DR revealed a more potent effect on I/R injury via the additive effect of DLA and R1, which not only inhibited apoptosis caused by low expression of Sirt-1/NDUFA10/Complex I, but also inhibited myocardial fiber fracture caused by RhoA/ROCK1 activation and decreased expression of ATP/ATP5D/Complex V.